A novel technique to quantify aortic valve annulus deformation: A pilot study. Issue 9 (11th June 2022) - Holst, Theresa; Petersen, Johannes; Adam, Gerhard; Reichenspurner, Hermann; Girdauskas, Evaldas; Tahir, Enver
Abstract: Objectives: We evaluated the potential of cardiac magnetic resonance (CMR)‐derived strain to assess aortic valve (AV) annulus deformation during the cardiac cycle in regurgitant and well‐functioning AVs. Methods: Four patients with severe aortic regurgitation and seven healthy controls underwent CMR. Assessment of longitudinal strain was performed by hypothesizing the AV annulus would be the left ventricle in long‐axis orientation. Longitudinal strain of the segments belonging to the muscular and fibrous AV annulus was weighted and averaged to obtain regional values (RLS). Results: Comparison of RLS between regurgitant and well‐functioning AVs showed a considerably different deformation of the muscular AV annulus (i.e., median RLS: 4.18 % [patients] vs. −10.41 % [controls], p  = .024). The fibrous AV annulus demonstrated comparable deformational changes in both groups. Conclusion: CMR‐derived strain allows for quantification of AV annulus deformation during the cardiac cycle and shows an altered RLS in the muscular AV annulus in patients with severe aortic regurgitation.